Kompakte lae-verlies diplekser met gestapte transmissielyn resoneerder - Anthonissen, Lukas Willem (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Ing.) -- Universiteit van Stellenbosch, 1993.